Finding margaret fuller eaudiobook A novel. - Pataki, Allison (Books on Tape, 2024)
A “sweeping” ( Entertainment Weekly ) novel of America’s forgotten leading lady, the central figure of a movement that defined a nation—from the New York Times bestselling author of The Magnificent Lives of Marjorie Post “ Soul-stirring . . . brings to life the epic and inspiring story of an incredible woman who should never be forgotten.” —Kristin Harmel, author of The Paris Daughter In the company of Ralph Waldo Emerson and his circle of enlightened friends, the young, beautiful, and brilliant Margaret Fuller becomes “the radiant genius and fiery heart” of the Transcendentalists. She inspires Louisa May Alcott, sparks Nathaniel Hawthorne to create Hester Prynne, and forms close bonds with Henry David Thoreau and Emerson himself. However, Margaret’s soul yearns for more than poetry and drama, leading her on a journey of adventure and self-discovery. From hosting a women-only literary salon in Boston to becoming the first woman permitted entry to Harvard’s library, Margaret defies societal conventions as an activist for women’s rights and a champion for humanity. On the gritty New York streets, she spars with Edgar Allan Poe and reports on the work of Frederick Douglass. And when offered an assignment in Europe by editor Horace Greeley, Margaret becomes the first female foreign news correspondent, mingling with the likes of Frédéric Chopin, William Wordsworth, and George Sand. In Rome, she embarks on a passionate love affair with a Roman count, causing an international scandal. As a mother and a countess, Margaret enters a new fight for Italy’s unification. With a star-studded cast and an epic sweep of historical events, this is a story of an inspiring trailblazer, a woman who loved big and lived even bigger—a fierce adventurer who transcended the rigid roles ascribed to women and changed history for millions, all on her own terms.